2022
DOI: 10.1212/wnl.0000000000200583
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Social Isolation and Loneliness With Later Dementia

Abstract: ObjectiveTo investigate the independent associations of social isolation and loneliness with incident dementia and to explore the potential neurobiological mechanisms.MethodsWe utilized the UK Biobank cohort to establish Cox proportional hazard models with social isolation and loneliness as separate exposures. Demographic (sex, age and ethnicity), socioeconomic (education level, household income and Townsend deprivation index), biological (BMI, APOE genotype, diabetes, cancer, cardiovascular disease and other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
69
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(92 citation statements)
references
References 55 publications
(83 reference statements)
2
69
3
1
Order By: Relevance
“…The COVID-19 pandemic and the resulting psychological problems pose an unprecedented health crisis and challenge for university students, who are a special group in the context of public health emergencies (Stowe et al, 2020). It has also been shown that people who are socially isolated have poorer cognitive skills, including memory and reaction time, and lower gray matter volume in many parts of the brain (Shen et al, 2022). Self-efficacy, the core concept of Bandura's social cognition theory (Bandura, 1997), refers to the judgments and beliefs that individuals have regarding their ability to organize themselves to perform actions and achieve their goals.…”
Section: Introductionmentioning
confidence: 99%
“…The COVID-19 pandemic and the resulting psychological problems pose an unprecedented health crisis and challenge for university students, who are a special group in the context of public health emergencies (Stowe et al, 2020). It has also been shown that people who are socially isolated have poorer cognitive skills, including memory and reaction time, and lower gray matter volume in many parts of the brain (Shen et al, 2022). Self-efficacy, the core concept of Bandura's social cognition theory (Bandura, 1997), refers to the judgments and beliefs that individuals have regarding their ability to organize themselves to perform actions and achieve their goals.…”
Section: Introductionmentioning
confidence: 99%
“…What follows becomes an intellectual challenge to reveal the substructure of social isolation and identify those elements most relevant to dementia risk. Emotional components in light of the Shen et al 3 study seem less important than supposed. The problem might be resolved using psychometric methods to uncover latent factors modulating cognitive impairments seen more often among the socially isolated and show their relevance to dementia risk.…”
mentioning
confidence: 79%
“…By itself, this is a useful conclusion, consolidating earlier work, and translates easily into community actions to address health concerns of old people living socially isolated lives. But Shen et al 3 go further and explore this association in ways anticipated by Siebner et al 1 They show that social isolation can be linked to lower than expected GM volumes in brain structures already implicated in the pathogenesis of AD signs and symptoms. Their analytical model was then extended to show underexpression of AD-related genes in participants with identified GM reductions.…”
mentioning
confidence: 97%
See 2 more Smart Citations